Legal Protection for Land Buyers in Sale and Purchase Agreement Under Hand - Lewaherilla, Imanuel David Jackson; Akyuwen, Rory Jeff; Radjawane, Piter (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Land rights acquisition can be obtained in various ways such as buying and selling, exchanging, granting or bequests, but the acquisition of land rights that often occurs in society is through buying and selling.Purposes of the Research: The purpose of this study is to examine the legal force of the transfer of land rights through underhand sales and legal protection for the purchaser of land rights through underhand sales.Methods of the Research: The research method used in this writing is normative legal research by using analytical descriptive research on legal regulations and expert opinions through primary, secondary and tertiary legal materials through the process of collecting legal materials and analyzing them to obtain conclusions and suggestions.Findings of the Research: In the process of buying and selling land, it is very important to pay attention to the legal force in the buying and selling process, where if the buying and selling process is only carried out underhand, it can have an impact on the legal force of the buying and selling that is carried out because underhand buying and selling often does not have an authentic deed so that it is vulnerable to proof if a dispute occurs in the future and if there has been a sale and purchase underhand, the buyer must pay attention to several aspects in order to get legal protection in the buying and selling process, including the buying and selling process must be carried out at the village/district office in order to get supervision from the authorities and several witnesses must be present in the buying and selling process and this buying and selling process must be recorded.